From mice to men: Murine models of colorectal cancer for use in translational research. (February 2016) - Evans, Jonathan P.; Sutton, Paul A.; Winiarski, Boleslaw K.; Fenwick, Stephen W.; Malik, Hassan Z.; Vimalachandran, Dale; Tweedle, Elizabeth M.; Costello, Eithne; Palmer, Daniel H.; Park, B. Kevin; Kitteringham, Neil R.
Abstract: Colorectal cancer (CRC) is the third most common carcinoma worldwide and despite advances in treatment, survival for patients with metastatic disease remains poor. With nearly 50% of patients developing metastases, in vivo investigation is essential to improve outcomes for these patients and numerous murine models of CRC have been developed to allow the study of chemoprevention and chemotherapy, in addition to improving our understanding of the pathogenesis of CRC. Selecting the most appropriate murine model for a specific application will maximize the conversion of potential therapies from the laboratory to clinical practice and requires an understanding of the various models available. This review will provide an overview of the murine models currently used in CRC research, discussing the limitations and merits of each and their most relevant application. It is aimed at the developing researcher, acting as a guide to prompt further reading in planning a specific study.